1998
DOI: 10.1093/humrep/13.7.1825
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of subtle oocyte or sperm dysfunction affecting fertilization in endometriosis-associated or unexplained infertility: a controlled comparison with tubal infertility and use of donor spermatozoa

Abstract: This study aims to determine the relative contribution of oocyte and/or sperm dysfunction to the reduction of fertilization rates in vitro in cases of minor endometriosis and prolonged unexplained infertility. The results of in-vitro fertilization (IVF) treatment with ovarian stimulation have been compared between couples with the above conditions and women with tubal infertility (as control for oocyte function) and the use of donor spermatozoa (as control for sperm function). Fertilization and cleavage rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 32 publications
6
55
0
3
Order By: Relevance
“…It is cyclically expressed in the adult endometrium in response to steroid hormones, regulating endometrial receptivity during the nidation window [15]. Several studies have suggested an impairment of implantation in patients with endometriosis, but the mechanisms underlying it are not well understood [16][17][18]. In accordance with HOXA10's role in implantation, it was found that women with endometriosis have altered expression of HOXA10 in the eutopic endometrium, which could account for the defective implantation observed in these women [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is cyclically expressed in the adult endometrium in response to steroid hormones, regulating endometrial receptivity during the nidation window [15]. Several studies have suggested an impairment of implantation in patients with endometriosis, but the mechanisms underlying it are not well understood [16][17][18]. In accordance with HOXA10's role in implantation, it was found that women with endometriosis have altered expression of HOXA10 in the eutopic endometrium, which could account for the defective implantation observed in these women [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported a reduced fertilization rate with IVF in women with endometriosis [2,[8][9][10][11][12][13][14]. Pal et al (1998) reported a significant reduction in fertilization rates in stage III and IV of endometriosis compared with stage I and II.…”
Section: Introductionmentioning
confidence: 99%
“…Clear mechanisms causing the endometriosis-associated infertility have not been firmly established. Infertility in women with endometriosis may be associated with subtle, explicit or multifaceted abnormalities [1][2][3][4][5][6][7][8]. Anomalies have been identified in the ovary such as reduced rates of follicular growth, functional capacity of the preovulatory follicle, and early luteal function [1,2,4,5]; in gametes and embryos, including reduced rates of fertilization and defects in embryo development [1,6,[8][9][10]; and in endometrial function [7,11].…”
Section: Introductionmentioning
confidence: 99%